Alcohol-induced miR-155 and HDAC11 inhibit negative regulators of the TLR4 pathway and lead to increased LPS responsiveness of Kupffer cells in alcoholic liver disease. Issue 2 (5th June 2017) - Bala, Shashi; Csak, Timea; Kodys, Karen; Catalano, Donna; Ambade, Aditya; Furi, Istvan; Lowe, Patrick; Cho, Yeonhee; Iracheta-Vellve, Arvin; Szabo, Gyongyi
Abstract : Alcohol downregulates IRAK-M, SHIP1, SOCS1, and IL-10, inhibitors of TLR4 signaling, via NF-κB-induced miR-155 and HDAC11 in Kupffer cells. Abstract: Inflammation promotes the progression of alcoholic liver disease. Alcohol sensitizes KCs to gut-derived endotoxin (LPS); however, signaling pathways that perpetuate inflammation in alcoholic liver disease are only partially understood. We found that chronic alcohol feeding in mice induced miR-155, an inflammatory miRNA in isolated KCs. We hypothesized that miR-155 might increase the responsiveness of KCs to LPS via targeting the negative regulators of LPS signaling. Our results revealed that KCs that were isolated from alcohol-fed mice showed a decrease in IRAK-M, SHIP1, and PU.1, and an increase in TNF-α levels. This was specific to KCs, as no significant differences were observed in these genes in hepatocytes. We found a causal effect of miR-155 deficiency on LPS responsiveness, as KCs that were isolated from miR-155 KO mice showed a greater induction of IRAK-M, SHIP1, and suppressor of cytokine signaling 1 after LPS treatment. C/EBPβ, a validated miR-155 target, stimulates IL-10 transcription. We found a higher induction of C/EBPβ and IL-10 in KCs that were isolated from miR-155 KO mice after LPS treatment. Gain- and loss-of-function studies affirmed that alcohol-induced miR-155 directly regulates IRAK-M, SHIP1, suppressor of cytokine signaling 1, and C/EBPβ, as miR-155 inhibition increased and miR-155 overexpression decreased these genes in LPS or alcohol-pretreated wild-type KCs. HDAC11, a regulator of IL-10, was significantly increased and IL-10 was decreased in KCs that were isolated from alcohol-fed mice. Functionally, knockdown of HDAC11 with small interfering RNA resulted in an IL-10 increase in LPS or alcohol-pretreated Mϕ. We found that acetaldehyde and NF-κB pathways regulate HDAC11 levels. Collectively, our results indicate that the alcohol-induced responsiveness of KCs to LPS, in part, is governed by miR-155 and HDAC11.